Predictive toxicology : from vision to reality - Pfannkuch, Friedlieb; Suter-Dick, Laura; Mannhold, Raimund, 1948-; Kubinyi, Hugo.; Folkers, Gerd. (Weinheim : Wiley-VCH, 2014)
Tailored to the needs of drug developers, this one-stop reference for medicinal chemists covers all the latest developments in the field of predictive toxicology and its applications in safety assessment. With a keen emphasis on novel approaches, the topics have been tackled by selected expert scientists, who are familiar with the theoretical scientific background as well as with the practical application of current methods. Emerging technologies in toxicity assessment are introduced and evaluated in terms of their predictive power, with separate sections on computer predictions and simulation.
Introduction to Predictive Toxicology Tools and Methods / Laura Suter-Dick, Friedlieb Pfannkuch -- Toxicology : Current Approaches and Future Perspectives to Predict Toxic Effects with Computational Tools / Thomas Steger-Hartmann -- Approaches: Data Management : Bioinformatics / Arnd Brandenburg, Hans Gmuender, Timo Wittenberger -- Role of Modeling and Simulation in Toxicology Prediction / Antje-Christine Walz, Hans Peter Grimm, Christophe Meille, Antonello Caruso, Neil Parrott, Thierry Lave -- Genomic Applications for Assessing Toxicities of Liver and Kidney Injury / Philip Hewitt, Esther Johann -- Use of Toxicogenomics for Mechanistic Characterization of Hepatocarcinogens in Shorter Term Studies / Heidrun Ellinger-Ziegelbauer -- Discovery and Application of Novel Biomarkers / Timothy W Gant, Emma L Marczylo, Martin O Leonard -- Predictive Toxicology: Genetics, Genomics, Epigenetics, and Next-Generation Sequencing in Toxicology / Tobias Heckel, Laura Suter-Dick -- Biomarkers as Tools for Predictive Safety Assessment: Novel Markers of Drug-Induced Kidney Injury / Angela Mally -- The Use of Renal Cell Culture for Nephrotoxicity Investigations / Anja Wilmes, Paul Jennings -- The Zebrafish Model in Toxicology / Natalie Mesens -- Predictive Method Development: Challenges for Cosmetics and Genotoxicity as a Case Study / Gladys Ouedraogo, Fabrice Nesslany, Sophie Simar, Smail Talahari, Doris Lagache, Eric Vercauteren, Lauren Nakab, Astrid Mayoux, Brigitte Faquet, Nicole Flamand -- Using Pluripotent Stem Cells and Their Progeny as an Model to Assess (Developmental) Neurotoxicity / Lisa Hoelting, Marcel Leist, Luc Stoppini -- Stem Cell-Based Methods for Identifying Developmental Toxicity Potential / Jessica A Palmer, Robert E Burrier, Laura A Egnash, Elizabeth LR Donley -- Immunogenicity of Protein Therapeutics: Risk Assessment and Risk Mitigation / Harald Kropshofer -- Regulatory Aspects / Beatriz Silva Lima.
Includes bibliographical references and index.
Print version record.
Keywords: Toxicology; MEDICAL -- Pharmacology; Toxicology; Electronic books